A review of WAAM for steel construction – Manufacturing, material and geometric properties, design, and future directions. (October 2022) - Evans, Sian I.; Wang, Jie; Qin, Jian; He, Yongpeng; Shepherd, Paul; Ding, Jialuo
Abstract: This paper provides a review of the capabilities of WAAM for manufacturing steel components for use in the construction industry, with a focus on the structural stability and design of WAAM builds. Manufacturing techniques that can be used for WAAM construction are first discussed. This is followed by a detailed review of the material and geometric properties, and the resulting structural stability performance of WAAM steel structures to date. To exploit the advantage of WAAM in building free-form shapes, structural optimisation techniques suitable for WAAM construction are discussed. Lastly, conclusions and future research directions are provided.